Etnobotani Pemanfaatan Tumbuhan Sebagai Motif pada Ecoprint Bangka - Sulastri, Neli; Henri, Henri; Akbarini, Dian (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
Ecoprint is a technique for making motifs on fabrics or other environmentally friendly media, using only natural materials, namely plant parts of various species. The use of plants for ecoprint motifs is one of the implementations of ethnobotany in textile motifs. This research aims to determine techniques for making motifs that are more environmentally friendly and various types of plants that can be utilized. The research method used is descriptive qualitative, data collection using interviews, observation, documentation, and field sampling. The ecoprints techniques used are pounding, steaming, and boiling. The research results found 50 species of plants that could be used as motifs in ecoprints from 26 families. The highest score was from family Euphorbiaceae with as many as 10 species. The motifs produced are 60 motifs, with 68.3% using the steam technique,  20% the pounding technique, and 11.7% using the boiling technique. The most widely used plant part is the leaf as much as 80% and is the main characteristic of the motif in ecoprints. The introduction of ecoprints was carried out in various circles to expand public knowledge and interest in environmentally friendly products.Keywords - Ecoprint, Motif, Textile, Natural Material, Ethnobotany